2006
DOI: 10.1111/j.1349-7006.2006.00322.x
|View full text |Cite
|
Sign up to set email alerts
|

High expression of insulin‐like growth factor binding protein‐3 is correlated with lower portal invasion and better prognosis in human hepatocellular carcinoma

Abstract: H epatocellular carcinoma (HCC) is one of the most common and aggressive malignant tumors worldwide. The longterm prognosis of HCC patients has remained unsatisfactory due to the high incidence of intrahepatic recurrence, which depends on portal venous invasion and the high incidence of intrahepatic metastasis, as well as multicentric development of new tumors.(1,2) Moreover, our understanding of the molecular mechanisms underlying the progression of HCC and the development of effective therapeutic targets rem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
46
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(52 citation statements)
references
References 29 publications
6
46
0
Order By: Relevance
“…In agreement with these results, Aishima et al (20) showed an insignificant negative correlation between HCC staging and serum IGFBP-3 and IGF-1 levels. Moreover, in the present study, IGFBP-3 levels significantly discriminated between cirrhosis and HCC at a sensitivity of 87%, specificity of 80% and a cut-off value of <682.6 ng/ml.…”
Section: Discussionsupporting
confidence: 76%
“…In agreement with these results, Aishima et al (20) showed an insignificant negative correlation between HCC staging and serum IGFBP-3 and IGF-1 levels. Moreover, in the present study, IGFBP-3 levels significantly discriminated between cirrhosis and HCC at a sensitivity of 87%, specificity of 80% and a cut-off value of <682.6 ng/ml.…”
Section: Discussionsupporting
confidence: 76%
“…Santosh et al (33) reported that IGFBP-3 overexpression in tumor tissues was an independent predictor of reduced survival rate in patients with newly diagnosed glioblastoma. By contrast, Aishima et al (34) identified that high expression levels of IGFBP-3 were independently associated with an improved survival rate in patients with hepatocellular carcinoma. In patients with squamous cell carcinoma of the tongue, IGFBP-3 expression was associated with favorable outcomes (35).…”
Section: Univariate Analysismentioning
confidence: 99%
“…In breast cancer tissue, high IGFBP-3 expression has been associated in some studies with markers of poor prognosis, and/or worse overall survival (Rocha, et al 1996;SheenChen, et al 2009;Vestey, et al 2005). However, a relationship with overall or disease-free survival has not always been seen in breast (Ren, et al 2007) or other cancers (Katsaros, et al 2001), and there is evidence that in some cancers, for example head and neck (Papadimitrakopoulou, et al 2006) and hepatoma (Aishima, et al 2006), low tissue IGFBP-3 expression is associated with poorer patient outcome. Clearly, tissue IGFBP-3 expression is only one of a multitude of factors that might influence the survival of cancer patients, but it is of interest that a Kaplan-Meier plot (Györffy, et al 2010) for women with basal-type breast cancers (that typically have high IGFBP-3 expression) shows a significantly lower probability of recurrence-free survival for patients whose tumors have high IGFBP-3 mRNA expression (n=478, hazard ratio= 1.6, logrank P=0.001) (Fig.…”
Section: Egfr Igf1r and Sphingosine Kinase Signalingmentioning
confidence: 99%